Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in international development practice for over a decade. Learning-by-doing is a crucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporating data collection processes that generate useful, timely and practical information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in Mozambique. MUVA, we suggest, is atypically evidence-led. It combines systematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring, evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, how MEL systems are designed to prioritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of funders.This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclude by considering the relevance, or not, of MUVA’s approach to programmes in other contexts or issue areas trying to replicate a similarly evidence-informed approach to adaptive management. Key messages Learning-by-doing is essential to adaptive programming, but it can be challenging to establish data collection processes that generate useful, timely and practical information. MUVA – a female economic empowerment programme in Mozambique – has an atypically evidence-led adaptive management approach. This has two fundamental features. One, data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of implementing staff than to the reporting requirements of funders. Monitoring, evaluation and learning (MEL) systems are designed to prioritise actionable learning. This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Itad, Oxfam and IDS, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Nimble adaptation: Tailoring monitoring, evaluation, and learning methods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitoring, Evaluation, and Learning (MEL) systems within complex international development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evidence of theories of change, and contextual and politically contingent nature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse operating contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The authors analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in complex environments? (2) What is practical guidance for designing and enabling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Information gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moments of varying frequency and intensity, as well as multiple feedback mechanisms; and (3) Enabling structures that promote adaptive mindsets and attitudes within project teams.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20523

Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project, and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and resource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology. 2) Examine how adaptive management has been applied in EOL project implementation thus far. 3) Explore ways in which an adaptive management approach can be used as a source of learning during project implementation. 4) Propose ways in which the application of adaptive management can be improved in EOL project implementation. Objective 1: Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology: The researchers asessed whether the EOL program, GMU, and HESA RMU have a culture of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based staff and project officers. In addition, they looked at processes to assess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among grantees/ employees of the decision-making process. Summary of findings: Understanding of adaptive management as a programming approach among the selected sample of grantees was linked to continuous learning, the ability to adjust implementation and inform decision making to reach the intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a culture of openness where grantees feel comfortable sharing their opinion and ideas and is perceived to be receptive to proposed changes to projects and encourage grantees to provide feedback. The HESA RMU-Oxfam Denmark is also seen as an agency that is very “flexible“. Recommendations: Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive management which scans the horizon for opportunities and risks, and it adapts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key objectives of the management effort. Objective 2: Examine how adaptive management has been applied in EOL project implementation thus far Methodology: Two elements were assessed : Collaboration and how internal and external collaboration of grantees and grant agent, assessing the ability to collaborate with other departments within the entity, the ability to collaborate with learning partners, other grantees, to what extent they consult their stakeholders and their ability to build coalitions. In addition, researchers looked at Adaptation and the best practices and lessons learned in adopting change in the design, implementation, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learning, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emerging needs of EOL Program implementation. There is a simple process in place for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well and what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be encouraging learning practices through organizing periodic online and offline regional learning and reflection workshops. Compared to other donors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necessity for advocacy work. However, it is important to enforce structure to tighten the feedback loop between data and action: adaptive management aims for double learning more than just correcting deviations in planned versus actual. Recommendations: Introducing outcome harvesting tool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to examine the program’s role in making future events happen, enforcing structure to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and information gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implementation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during project implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to use learning to inform decision making, the frequency and habit of reviewing their theory of change, the risks and opportunities through scenario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they have a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program has adopted Re-active Adaptive Management that relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adaptive management and learning to other partners in targeted countries (EOL to become an influencer in this field), encouraging further engagement from learning partners to provide mentorship and support during implementation and continuous learning on adaptive management tools. RISP and GISP could be further engaged in the monitoring process. Based on the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This means AM will be expected to go beyond changing implementation strategies and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose ways in which the application of adaptive management can be improved in EOL project implementation Summary of findings: Grantees were able to articulate well their understanding of adaptive management but were less able to provide concrete examples of how adaptive management is implemented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten the feedback loop between data and action and to institutionalize practicing adaptive management. Recommendations: A roadmap that looks at reviewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design is needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced by HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1. Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positive or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from the monitoring data; Learning about the critical Make-or-Break assumptions in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, followed by analyzing and collective sense-making of possible implications for the Theory of Change (is there a need to revise intervention strategies, desired outcomes, pathways, assumptions? 4. Theory of change: Reviewing the theory of change was not seen as a frequently recommended practice. Constant validation of pathways to change and evidence in the TOC is important. 5. Capacity assessment and development: What capacities are available amongst the alliance members and partner organizations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learning so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflection?

OPM’s approach to assessing Value for Money - King, Julian; OPM (Oxford Policy Management, 2018)
This document offers practical guidance for assessing value for money (VfM) in international development programmes. Since 2016, evaluation expert Julian King has been working with OPM to develop and deploy a robust approach to VfM assessment. The approach combines cutting-edge evaluation practice with concepts from economic evaluation to respond to donor requirements for accountability and good resource allocation, as well as to support reflection, learning, and adaptive management.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Mainsreaming gender in an adaptive, politically smart governance programme - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks at the experience of gender mainstreaming in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • When development programmes try to engage with political stakeholders and align with the priorities of wider coalitions there is a danger that gender equality is de-prioritised. • It is important that formal political economy analysis, as well as other data collection, analysis and consultation exercises, are gender-sensitive. Teams should also look for ways to make gendered political and power analysis part of the everyday routine practice of staff. • Working politically and adaptively to advance gender objectives calls for staff with a specific skillset, as well as links to appropriate networks and political stakeholders. It also implies establishing checks and incentives to hold staff and partners accountable for gender objectives, and strong and consistent messaging from team leaders.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Working effectively through partnerships - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks critically at the approach to value for money (VfM) in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Adaptive, politically smart programmes like I4ID aim to deliver VfM by learning about what will work in complex environments, and quickly incorporating those lessons into delivery. When functioning properly, they can rapidly wind down activities as new information emerges and divert funding to more effective alternatives. • This means that adaptive programmes will achieve their potential to deliver strong VfM when their processes are good – when appraisal of experimental efforts is timely, consistent, knowledgeable and politically astute. As these programmes mature in their implementation phase, VfM evaluation should be focused on checking for a culture of adaptation and learning supported by strong adaptive processes. • While economy is important for adaptive programmes, it is also important that keeping costs low does not deprive teams of the resources, staff, and management and administration time they need to gather information, experiment, learn and adapt.

Adaptive Programming and Business Environment Reform – Lessons for DFID Zimbabwe - Donovan, Elbereth; Manuel, Clare (DFID, 2017)
Keywords: IMPORTANT

Lessons for Effective resilience programs: a case study of the RAIN program in Ethiopia - Kleiman, Shanti (Mercy Corps, 2013)
The RAIN program experience affirms the importance of multi-year and flexible funding as key program design features if progress in resilience building is to be supported in areas with high levels of structural and temporal vulnerability. These features enable management to respond effectively to changing circumstances in order to better meet the needs of communities and to create the necessary conditions for relief-to-development strategies to take hold. Finally, this study found that deliberate and effective coordination between donor agencies can ensure that development gains achieved during one program period are directly leveraged by subsequent programs, thereby increasing the effectiveness of resilience programs.

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/poms.13492

Nuru Kenya transition from Nuru International, Kenya - Dillan, Haley; Ouma, Joel; Yamron, David (What Transformation Takes - Evidence of Responsible INGO Transitions to Locally Led Development Around the World, 2020)
This case study is an example of a phased transfer of ownership and responsibility from INGO Nuru International to Nuru Kenya, including the exit of all international staff. Post-transition, Nuru Kenya is managed entirely by Kenyan staff, although it continues to receive financial support from Nuru International. A lot of the elements described are aligned with Adaptive Management ways of working.

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (Institute of Development Studies, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.
Accepted: 2022-05-10T09:42:35Z

The Boda Boda Talk Talk Module - Internews (Internews & USAID, 2017)
Keywords: IMPORTANT

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experiencing a learning crisis. Many efforts to address this crisis do not account for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcomes. Thinking through the feedback relationships that produce the education system can be challenging. The RISE Education Systems Framework, which is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be helpful. The RISE Framework identifies four key relationships in an education system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delegation, finance, information, support, and motivation. This Framework can be a useful approach for characterising the key actors and interactions in the education system, thinking through how these interactions produce systems outcomes, and identifying ways to intervene that can shift the system towards better outcomes.

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20474

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice